The Academia's Multidisciplinary Approaches in Providing Education, Scientific Training and Services to the Malaysian Halal Industry - Alina Abdul Rahim; H.K.M.W. Syamsul; A. Siti Mashitoh; M.H.M. Yusop; Norhayati Rafida Abdul Rahim (IDOSI Publications, 2024)
Non-Indexed Publication